2019
DOI: 10.1155/2019/8681959
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Glycemic and Lipid Profiles in Type 2 Diabetics with a 90-Day Ketogenic Diet

Abstract: Because low-carbohydrate diets are effective strategies to improve insulin resistance, the hallmark of type 2 diabetes, the purpose of reporting these clinical cases was to reveal the meaningful changes observed in 90 days of low-carbohydrate (LC) ketogenic dietary intervention in female type 2 diabetics aged 18-45. Eleven women (BMI 36.3 kg/m2) who were recently diagnosed with type 2 diabetes based on HbA1c over 6.5% (8.9%) volunteered to participate in an intensive dietary intervention to limit dietary carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 25 publications
4
48
1
1
Order By: Relevance
“…Therefore, the HbA1c level showed essential clinical significance in evaluating the blood glucose control, revealing the potential problems in the treatment and thereby guiding the therapeutic schedule 30,31 . Eight of the selected studies showed a reduction of HbA1c after KD consumption, the changes ranging from −0.6% to −3.3%; HbA1c reduced <1.5% in the majority of the studies included in the current analysis besides the study conducted by Walton (−3.3%; weight random 5.1%) 15 . The possible explanation for such strong improvement of HbA1c could be that Walton's study had enrolled a limited number of patients and thus the compliance of patients to KD therapy can be guaranteed.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the HbA1c level showed essential clinical significance in evaluating the blood glucose control, revealing the potential problems in the treatment and thereby guiding the therapeutic schedule 30,31 . Eight of the selected studies showed a reduction of HbA1c after KD consumption, the changes ranging from −0.6% to −3.3%; HbA1c reduced <1.5% in the majority of the studies included in the current analysis besides the study conducted by Walton (−3.3%; weight random 5.1%) 15 . The possible explanation for such strong improvement of HbA1c could be that Walton's study had enrolled a limited number of patients and thus the compliance of patients to KD therapy can be guaranteed.…”
Section: Discussionmentioning
confidence: 98%
“…Arguably the most significant and relevant therapeutic domain for nutritional ketosis is diabetes mellitus. In a recent small trial of patients with recently diagnosed type 2 diabetes, after 90 days of consuming less than 30 g of carbohydrate per day, mean weight loss was 9 kg, systolic and diastolic blood pressure reduced by 10.7 and 7.3 mmHg respectively, and mean Haemoglobin A1c (HbA1c) came down from 8.9% to 5.6% [78]. However, this study had just 11 patients and no control group, so while the validity of the findings is not in doubt, their generalizability and reproducibility remain to be determined.…”
Section: Clinical Effects Of Nutritional Ketosismentioning
confidence: 99%
“…In the brain, ketone bodies (such as β-hydroxybutyrate) contribute to sterol synthesis [34], which is essential for the growth of myelin membranes [55 (35)]. Studies have shown that diabetic patients can signi cantly increase HDL cholesterol and lower blood pressure through a 90-day KD diet, while LDL cholesterol shows no signi cant difference [36]. However, long-term ketogenic diet increases the risk of type 2 diabetes and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%